Multidecadal variability of Eastern Australian dust and Northern New Zealand sunshine: Associations with Pacific climate system - Lamb, P.; Leslie, Lance; Timmer, R.; Speer, M. (American Geophysical Union, 2009)
Central eastern Australia is a major global source region for atmospheric dust. Time series of surface dust observations show that a striking multidecadal oscillation of dust frequency has occurred in this large region since the late 1950s. From 1959 to 1973, there was a pronounced and consistent dust maximum, after which a sharp decline was followed by a much more dust-free 1977–2006. Time series of surface and 925 hPa (~725 m) winds reveal that the dust oscillation was associated locally with strengthening and then weakening of the southerly component of the low level wind over the dust-prone region. Composite maps for 1959–1973 (dusty) and 1977–2006 (more dust-free) indicate that these local wind changes reflected the relative speed of the southerly-southeasterly airflow into southeastern Australia. Correlation analyses show that this multidecadal regional wind oscillation was associated with similar timescale changes in the behavior of the Pacific climate system, including the latitudinal displacement of the South Pacific Convergence Zone, and more remotely with the sea surface temperature changes of the Pacific Decadal Oscillation (tropical North Pacific and extratropical North-Northeast Pacific) and North Pacific Oscillation (central subtropical North Pacific). Further correlation analyses suggest these Pacific climate system oscillations modulated other key environmental conditions (cloud regime, sunshine duration, rainfall rate) across the Southwest Pacific, including northern New Zealand sunshine.